Internalization of Antar Pakatan values in establishment of civic disposition - Hemafitria Hemafitria; Erna Octavia Octavia (Universitas Negeri Yogyakarta, 2021)
This study aims to provide a concept for the formation of civic Disposition through the Antar Pakatan culture that grows in the Sambas Malay community. Activities that have become a habit in this tradition are the basis for applying the values that shape character. In a qualitative approach to research, the method used is ethnography. Data collection through participatory observation and interviews with 11 community leaders, religious leaders, communities, and village heads. This data analysis technique consists of three paths: data reduction, data presentation, and concluding. Based on the findings of Antar Pakatan, some values shape citizenship attitudes, namely an increase in the sense of unity, social care, a system of cooperation values in the economic field that can become a harmonious character by strengthening the values of Pancasila. The attitude of citizenship through Antar Pakatan as an effort to implement meanings such as adaptation, prioritizing peace, namely the formation of democratic attitudes and social care and integration. It is to unify perceptions of the benefits of togetherness to form a sense of unity that creates social attitudes and harmonizes harmony between communities.